(untitled) (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2020)
This study aims to find out how the influence of the understanding of government accounting standards, organizational commitment and implementation of the code of ethics by the auditor’s regional inspectorate on the quality of the financial statements of Subang Regency.The population in this study was 60 Regional Work Units (SKPD) in Subang Regency. Sample size determination uses the Slovin formula so that the sample taken is 52 SKPD. The accounting department was chosen as the respondent in the study. The sampling method uses the proportionate stratified random sampling method. The data analysis technique used is multiple regression analysis with the help of IBM SPSS Statistics 22 for Windows. The results showed that partially or simultaneously the variable understanding of government accounting standards, organizational commitment and the application of the code of ethics by the auditor of regional inspectorates had a positive and significant effect on the quality of the financial statements of Subang Regency.